What the Owls Leave Behind: Pellet Size Variation Reflects Predator Body Size in Israel’s Owls - Ezra Hadad; Piotr Zduniak; Reuven Yosef (Ecologies)
Owl pellets offer a distinctive, noninvasive perspective on the feeding ecology and morphological traits of owl species. This study presents the first comprehensive comparison of pellet dimensions—specifically length, breadth, and mass—across all 11 resident owl species in Israel. A total of 816 pellets were collected from diverse habitats, including Mediterranean woodlands, agricultural landscapes, and arid deserts. Pellet measurements were analyzed in relation to the average body length of each species, revealing significant interspecific variation in all three dimensions. Statistical analyses confirmed strong positive correlations between body size and pellet length (r = 0.95), breadth (r = 0.91), and mass (r = 0.96), highlighting the influence of morphological constraints on pellet structure. Larger owls, such as Bubo bubo and B. ascalaphus, produced the largest pellets, whereas smaller species, such as Otus brucei and O. scops, generated notably smaller and lighter pellets, consistent with their known dietary preferences. Habitat differences and ecological specialization likely contribute to further variability in pellet morphology, even among closely related taxa. By focusing on pellet morphometrics rather than prey composition, this study offers a standardized and replicable method for interspecific comparisons. The findings support the use of pellet size as a proxy for predator body size and ecological strategies and provide a valuable baseline for future research on owl diets, habitat use, and species identification in the Middle East and elsewhere. This study enhances the utility of pellet analysis in both ecological monitoring and conservation biology.